Experimental study on the effect of Zfp260 on osteogenic differentiation, proliferation and migration of MC3T3-E1 cells in vitro - WU Jun; WANG Zuolin (Kouqiang hemian waike zazhi)
[Objective:] To explore the effect of zinc‐finger protein 260 (Zfp260) on the osteogenic differentiation, proliferation and migration of mouse embryo osteoblast precursor cells (MC3T3-E1 cells) in vitro. [Methods:] MC3T3-E1 cells were cultured in vitro and induced to differentiate into osteoblasts. The expression of Zfp260 was detected by real-time quantitative polymerase chain reaction (RT-qPCR) when it was induced for 7 days and 14 days. MC3T3-E1 cells were transfected with siRNA, and the knockdown efficiency of Zfp260 and the expression of alkaline phosphatase (ALP), human bone morphogenetic protein 2 (BMP2) and other osteogenic biomarkers in knockdown group and control group were measured by RT-qPCR. The change of migration ability of MC3T3-E1 cells after knockdown of Zfp260 was detected by Transwell, cell scratch assay. The change of proliferation ability of MC3T3-E1 cells after knockdown of Zfp260 was detected by CCK8 experiment. [Results:] The expression of Zfp260 was significantly up-regulated after inducing osteogenic differentiation of MC3T3-E1 cells in vitro (P<0.05). After using siRNA to knock down Zfp260, the expression of ALP and BMP2 were significantly decreased (P<0.05). Transwell and cell scratch assays showed that the migration ability of MC3T3-E1 cells was inhibited after knocking down Zfp260. CCK8 experiment showed that the proliferation ability of MC3T3-E1 cells increased after knocking down Zfp260. [Conclusion:] Zfp260 can promote the osteogenic differentiation of MC3T3-E1 cells.